2021
DOI: 10.3390/ma14185448
|View full text |Cite
|
Sign up to set email alerts
|

Fractal Dimension and Texture Analysis of Lesion Autofluorescence in the Evaluation of Oral Lichen Planus Treatment Effectiveness

Abstract: Background: Oral Lichen planus (OLP) is a chronic inflammatory disease. Topical steroids are used as the treatment of choice. The alternative is photodynamic therapy (PDT). The study aimed to fabricate optimal biodegradable matrices for methylene blue or triamcinolone acetonide because of a lack of currently commercially available carriers that could adhere to the mucous. Methods: The study was designed as a 12-week single-blind prospective randomized clinical trial with 30 patients, full contralateral split-m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 53 publications
(53 reference statements)
0
3
0
Order By: Relevance
“…In our previous study, we confirmed a moderate negative correlation between FD of the surface lesion in the case of the potentially malignant lesion (oral lichen planus). In that study, we observed that the surface FD of lesions was significantly lower than normal mucous [ 55 ]. The analysis of the fractal dimension of the surface of the examined lesions turned out to be a less differentiating parameter than the fractal analysis of the lesion shape.…”
Section: Discussionmentioning
confidence: 99%
“…In our previous study, we confirmed a moderate negative correlation between FD of the surface lesion in the case of the potentially malignant lesion (oral lichen planus). In that study, we observed that the surface FD of lesions was significantly lower than normal mucous [ 55 ]. The analysis of the fractal dimension of the surface of the examined lesions turned out to be a less differentiating parameter than the fractal analysis of the lesion shape.…”
Section: Discussionmentioning
confidence: 99%
“…Although the present review focused on the diagnostic and prognostic value of fractal analysis in oral oncology, the literature reported some sporadic and preliminary works dealing with the monitoring of treatments as reported by the Polish group of Jurczyszyn et al [51,52], who applied fractal dimension and texture analysis of lesion autofluorescence in the evaluation of oral lichen planus treatment effectiveness and in estimating the effectiveness of oral leukoplakia treatment using the LiteTouch™ Er:YAG Dental laser, or by Varsha et al, who recently explored the pre-and post-treatment objective evaluation of remission in oral lichen planus using fractal analysis and compared it with the visual analog (VAS) scale [53].…”
Section: Future Directionsmentioning
confidence: 99%
“…This makes it possible to determine the percentage unhealed index (PUI), expressing the percentage of the lesion not healed at follow-up visits in relation to the baseline. The changes observed following treatment in the fractal dimension and texture (microcontrast) values of mucosal lesions on intraoral radiographs assessed under different light can be used to analyze the comparative effectiveness of treatment methods [113].…”
Section: Clinical Studiesmentioning
confidence: 99%